Architectural design techniques in organization of public spaces in dense urban building (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
Organization of public spaces features in conditions of dense urban development are considered in the article. The design of such spaces contributes to the formation of a friendly environment with a priority on the human scale. The experience of organizing public spaces has been analyzed. It has been established that modern trends in the design of open public spaces are aimed at creating physical, psychological and visual comfort for city residents. It was noted that two main types of actions take place in the public space: pedestrians' moving and staying. Such spaces are in constant connection with the surrounding buildings and interact with them in spatial planning and functional aspects. Depending on the urban planning situation, public space can be mono- or multi-functional. Three main architectural and design methods of organizing public space in dense buildings were identified during the research: abutment, intersection and centering. It has been noted that public spaces should have an expressive artistic image that helps to identify it and create a «living» center for city residents. Formation of urban interiors is related to existing situation analysis in a certain fragment of urban environment, identification of residents' actual needs, detailing of space due to subject filling. Attracting all the necessary means for the full functioning of public space and the ability to meet the needs of society in a quality environment is a priority task today and in the future. It is very important to create urban environment features of openness to public at the sidewalk levels. Public spaces in dense buildings can have quite a variety of configurations, despite planning and spatial limitations. Their design is based on an environmental approach and a detailed features study of socio-cultural processes that take place in a certain area.
Keywords: public space; urban environment; urban interior; human scale; dense building